The Effect Of Job Enlargement On The Work Satisfaction Of Front Office Employees Department At Amaris Hotel Diponegoro Yogyakarta - Riska Veronika; Anggun Sari Sasmita (Program Studi Hospitality dan Pariwisata, 2018)
ABSTRACT An organization is a group of people who interact and work together to realize common goals. The most important element in an organization is a group of people or human resources. One of the causes of employee dissatisfaction in work is doing the same basic task repeatedly. Therefore, job expansion or as known as job enlargement is developed to increase the number of tasks undertaken by workers. This study aims to determine the effect of job enlargement on job satisfaction of front office department employees at Amaris Hotel Diponegoro Yogyakarta. Independent variable studied is job enlargement (X) with dependent variable is job satisfaction (Y). This study uses saturated sampling in which the population is sampled. Data analysis techniques used are descriptive statistics, correlation analysis and coefficient of determination. Based on the result of research, the correlation value for job enlargement variable is 0.53. The coefficient of determination is 0.25 or 25%. The remaining 75% had an effect on other factors outside of this study.Keywords: job enlargement, job satisfaction, front office